Global Marketing Strategies / Third Edition - Hennessey David H; Jeannet Jean-Pierre (Houghton Mifflin Company, 1995)
Introduction, Understanding the Global Marketing Environment, The Global Economy, Cultural and Social Forces, Political and Legal Forces, Analyzing Global Marketing Opportunities, Global Markets and Buyers, International and Global Marketing Research, Developing Global Marketing Strategies, Developing a Global Mindset, Global Marketing Strategies, Global Market Entry Strategies, Designing Global Marketing Programs, Developing New Products for Global Markets, Procing for International and Global Markets, Managing International and Global Advertising, Managing the Global Marketing Effort, Practicing Global Marketing.
Introduction, Understanding the Global Marketing Environment, The Global Economy, Cultural and Social Forces, Political and Legal Forces, Analyzing Global Marketing Opportunities, Global Markets and Buyers, International and Global Marketing Research, Developing Global Marketing Strategies, Developing a Global Mindset, Global Marketing Strategies, Global Market Entry Strategies, Designing Global Marketing Programs, Developing New Products for Global Markets, Procing for International and Global Markets, Managing International and Global Advertising, Managing the Global Marketing Effort, Practicing Global Marketing.